2019
DOI: 10.3389/fpubh.2019.00055
|View full text |Cite
|
Sign up to set email alerts
|

How Can Physical Activity Be Promoted Among Children and Adolescents? A Systematic Review of Reviews Across Settings

Abstract: Introduction: A vast majority of children and adolescents are physically inactive. As a result, high obesity rates and related diseases have made physical activity promotion a politically relevant topic. In order to form the basis for political decision making, evidence is required regarding the efficacy and effectiveness of interventions for physical activity promotion. In contrast to previous research, this systematic review of reviews targets three key settings (family and home, childcare, school), and is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
166
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(183 citation statements)
references
References 91 publications
14
166
0
3
Order By: Relevance
“…In addition, it is a risk factor for which effective and cost-effective interventions are available. [26][27][28] Schooling had an effect independent of sex, age, physical activity level, and place of residence, with a higher risk in subjects belonging to a lower educational status, which demonstrated the importance of this social health determinant to improve the health actions. As indicated in previous publications, the identification of this type of health determinant is key for guiding programs focused on the prevention of health inequalities (in this case, in the distribution of metabolic syndrome) according to social status.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, it is a risk factor for which effective and cost-effective interventions are available. [26][27][28] Schooling had an effect independent of sex, age, physical activity level, and place of residence, with a higher risk in subjects belonging to a lower educational status, which demonstrated the importance of this social health determinant to improve the health actions. As indicated in previous publications, the identification of this type of health determinant is key for guiding programs focused on the prevention of health inequalities (in this case, in the distribution of metabolic syndrome) according to social status.…”
Section: Discussionmentioning
confidence: 89%
“…Given the importance of promoting physical activity among young people, researchers have sought to identify effective strategies and contexts to enhance physical activity in this population [12]. Physical education (PE) has been identi ed as a potentially viable existing network on which interventionists can capitalize to deliver physical activity interventions to a broad, diverse, and captive audience of young people [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Physical inactivity has emerged as a public health pandemic (Kohl 3rd et al, 2012) and internationally the prevalence of children participating in sufficient levels of physical activity remains low (Aubert et al, 2018). In response, researchers have developed and tested the effectiveness of numerous childhood physical activity interventions (Messing et al, 2019). Amidst some success, their impact has been limited (Longmuir & Tremblay, 2016;Love, Adams, & van Sluijs, 2019) and several research gaps remain.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of the determinants of physical activity in children aged 0-6 years found that parent monitoring was the only factor consistently associated with children's physical activity (Hesketh et al, 2017). More recently, a synthesis of results from 39 high-quality reviews (Messing et al, 2019) provided strong evidence that parents play a key role in promoting child physical activity across various community settings.…”
Section: Introductionmentioning
confidence: 99%